Menuju Implementasi Flexible Working Arrangement Ideal Pasca Masa Covid-19 : (Studi Praktek Terbaik Pada Kementrian Kelautan dan Perikanan) - Dida Daniarsyah; Nova Dwi Rahayu (Universitas Serang Raya, 2020)
This article tries to analyse the implementation of the Flexible Working Arrangement (FWA) and identify the ideal FWA model. The research problem raised in the ongoing FWA implementation that does not yet have a minimum FWA standard by academic or philosophical concepts. FWA at the Ministry of Maritime Affairs and Fisheries is suspected of being unplanned and aims merely to prevent employees from contracting co-19. The research method uses a descriptive qualitative approach. Primary data sourced from interviews, observations, documentation. The study results concluded that FWA implementation is still limited to moving attendance from the office to the home through the WFH scheme and tends to be forced. Without planning, employees do not understand the ideal WFH concept. WFH that has been taking place at KKP can be adequately developed into an ASN work system model with broader schemes such as job sharing and flexi-time. The success of the WFH implementation depends very much on supporting mobile and HP mobile devices for Zoom Applications and the like, the availability of internet data packages, and the network infrastructure condition at the WFH location. The suggestions from the study results are psychological needs in managing work behavior to be productive by formulating an ideal FWA model that considers factors, impacts, implementation, and benefits to achieve effective, efficient, productive, and contributed.